A general survey and some taxonomic implications of diterpenes in the Asteraceae - Alvarenga, SAV; Ferreira, MJP; Rodrigues, G. V.; Emerenciano, V. P. (Blackwell Publishing, 2005)
This paper provides a general survey of the occurrence of diterpenes in the Asteraceae. Data on 4351 botanical occurrences were obtained from the literature. These were grouped by skeleton for each genus. Then, the genera were grouped by subtribes, which, in turn, were gathered in tribes, followed by subfamilies. In spite of the low number of species containing diterpenes, it was possible to describe some structural features of these compounds, i.e. The skeletal types in various taxa and the positions in some skeletons that are always oxidized or never undergo oxidation in some genera. Thus, it was verified that: in the subfamily Cichorioideae, only a few of the studied species possess diterpenes, wherein kaurane is the most frequent diterpene skeleton. In the Asteroideae, the presence of diterpenes is much greater than that in the Cichorioideae and Carduoideae. At tribal taxonomic level, for example, the Astereae produce labdanes and clerodanes; Heliantheae and Eupatorieae produce kauranes and labdanes, respectively; and Calenduleae produce pimaranes. Some taxonomic implications are presented. (c) 2005 the Linnean Society of London.
Keywords: chemotaxonomic marker; diterpenoids; natural products